Gemcitabine combined with the monoclonal antibody nimotuzumab is an active first-line regimen in KRAS wildtype patients with locally advanced or metastatic pancreatic cancer: a multicenter, randomized phase IIb study - Schultheis, Beate; Hofheinz, Ralf-Dieter (Annals of oncology, 2017)
AbstractBackground. This randomized study was designed to investigate the superiority of gemcitabine (gem) plus nimotuzumab (nimo), an anti-epidermal growth fa